Research of the Optimizing of Urban Bus Drive Axle - Zhou Chi; Wang Tie; Liu Yaqiong; Liu Baoqian; Chen Haoli (Jixie chuandong)
The vibration of an urban bus is abnormal during the process of driving,the reason may be that the drive axle is the resonance of drive axle.Through the method of modal test and finite element analysis,the intrinsic mode characteristic of drive axle are obtained,and comparing with the excitation frequency that may caused the drive axle resonance,found that the main reduction gear meshing frequency and the drive axle low order natural frequency are coupling when the engine and transmission in common use.By using finite element method,taking improving the low natural frequency of drive axle as the target,the mass and strength as the constraints condition,the optimization design is conducted.The result is that the improvement of drive axle dynamic characteristic is obviously,the meshing frequency of main reduction gear is effectively avoided.